2018
DOI: 10.1016/j.antiviral.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of maribavir in combination with other drugs active against human cytomegalovirus

Abstract: The human cytomegalovirus (CMV) UL97 kinase inhibitor maribavir is in Phase III clinical trials as antiviral therapy, including use for infections refractory or resistant to standard therapy. To assess its activity in combination with approved and experimental CMV antivirals, and with the mTor inhibitor rapamycin (sirolimus), drug effects were tested by in vitro checkerboard assays and the data were analyzed using a three dimensional model based on an independent effects definition of additive interactions. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 37 publications
2
43
0
Order By: Relevance
“…The use of rapamycin for the GVHD prophylaxis in patients with a reduced intensity conditioning (20% of the patients treated with ATG and 60% of the whole series) may be another explanation for this lack of association. Results not published yet from our laboratory show an anti-HAdV activity of rapamycin, with an IC 50 of 2.3 µM (selective index of 55), as it had been reported for HCMV (12). The lack of association with any demographic data, transplantation or clinical characteristics was independent of the level of HAdV viremia (data not shown).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…The use of rapamycin for the GVHD prophylaxis in patients with a reduced intensity conditioning (20% of the patients treated with ATG and 60% of the whole series) may be another explanation for this lack of association. Results not published yet from our laboratory show an anti-HAdV activity of rapamycin, with an IC 50 of 2.3 µM (selective index of 55), as it had been reported for HCMV (12). The lack of association with any demographic data, transplantation or clinical characteristics was independent of the level of HAdV viremia (data not shown).…”
supporting
confidence: 66%
“…Results from our laboratory not yet published show an anti- HAdV activity of rapamycin, with an IC50 of 2.3 mM (selective index of 55), as reported for human cytomegalovirus (HCMV). 12 The lack of association with any demographic data, transplantation or clinical characteristics was independent of the level of HAdV viremia ( data not shown ).…”
mentioning
confidence: 89%
“…This likewise holds true for many other mechanistically distinct, additive drug combinations, including GCV, which may nevertheless prove beneficial as new HCMV treatments and therefore merit a closer investigation in clinical approaches. As the computer-assisted prediction of a truly synergistic drug combination, however, is almost impossible, an experimental assessment based on the two applied approaches is crucial for ensuring reliability [ 26 , 27 , 65 ]. In the present study, we identified strong synergism between the two PKIs MBV and LDC4297, constituting a very promising experimental outcome of combinatorial assessment.…”
Section: Resultsmentioning
confidence: 99%
“…differences in substrate binding, nuclear translocation and drug susceptibility [44,70] [ [71][72][73][74] Similarity and sequence conservation with other kinases low <35% identity with herpesviral kinases, <15% identity with cellular kinases [45,63] [ [48][49][50]75] Sequence conservation ORF-UL97 of HCMVs high no variation of translational start sites, NLS sequences or kinase domains [44] [ 76,77] Related to cell kinases cyclin-dependent kinases (CDKs), viral CDK ortholog functional overlap with CDKs, specific crosstalk with CDK9, CDK7 and CDK1, direct interaction with cyclins [47,55,56,[78][79][80][81][82][83] [57, 84,85] Coregulation of viral replication by pUL97 and cellular kinases several novel cellular kinases, including CDKs, identified to be involved in HCMV replication virus-supporting functions in signaling pathways and nuclear capsid egress [55,56,86,87] [ [88][89][90][91][92][93] Substrate proteins viral, cellular pUL44, pUL69, pp65, Rb, p32/gC1qR, nuclear lamins, EF-1δ, RNAP II, IFI16, SAMHD1 [53,79,87,[94][95][96]…”
mentioning
confidence: 99%